KANDUNGAN UNSUR HARA PADA SERASAH DAUN SEGAR POHON (MAHONI, NANTU DAN MATOA) - Wowor, Andre E.; Thomas, A.; Rombang, J. A. (Universitas Sam Ratulangi, 2019)
Plant life cycle requires adequate nutrient content in the planting media environment. Nutrients are naturally influenced by cyclical nutrition itself. Plants in the form of trees play a role in the synthesis of nutrients themselves. Trees play a role in absorbing nutrients in the soil and releasing nutrients through dead or harvested tissue, plant tissues that are most often canceled or killed because the weather is leaves. The nutritional needs of trees are different so the absorption, use and management of nutrients in trees is also different. The purpose of this study is to see the differences in species of Mahogany, Nantu and Matoa trees, which has the potential to contribute to the availability of nutrients. The method used in the study was a completely randomized design (CRD) with three replications. Analysis of nutrient N, P and K was carried out in the laboratory using extraction of perhydrol by wet ingestion of H2SO4+H2O2. The results of the research obtained, that the fresh leaf litter of the nantu tree is the most potential as a nutrient-contributing tree to the surface soil.